Impact of creative workshops in an institutionalized patient with moderate/severe cognitive impairment with behavioral disorders: A case report - Bravo-Garrido, Nuria; Morán-Cortés, Juan Francisco; Coronado-Vázquez, Valle; Ramírez-Durán, María del Valle (Frontiers in Psychiatry, 2023)
The Hospital Care Unit for individuals with intellectual disabilities and behavioral disorders provides comprehensive care in a controlled and video-surveyed facility that minimizes access to potentially manipulative materials during aggression or pica episodes. The patient was admitted to the unit due to issues including ingestion of non-edible fluids, aggression towards staff and other patients, and self-injury. All patients participated in occupational activities led by an occupational therapist from Monday to Friday from 10 am to 11:30 am. In addition, creative workshops such as cinema forums and cooking workshops were held on some afternoons. During the analyzed period from January to June 2022, the patient experienced three episodes of pica, 14 assaults towards staff, and eight towards peers. All of these incidents occurred after dinner and were triggered either by the inability to eat dessert or by refusal to brush her teeth afterwards. In our case study, the implementation of creative workshops such as cooking had a positive effect on decreasing instances of pica and aggression. These workshops slightly improved participation in other occupational therapy activities and stabilized the patient's behavior, increasing the likelihood of her being able to return to her normal residence.